2018
DOI: 10.5334/ijic.3432
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Relational Ties in Inter-Professional Teams in Norwegian Specialized Health Care: A Multicentre Study of Relational Coordination

Abstract: Introduction:The delivery of integrated care depends on the quality of communication and relationships among health-care professionals in inter-professional teams. The main aim of this study was to investigate individual and team communication and relational ties of teams in specific care processes within specialized health care.Methods:This cross-sectional multi-centre study used data from six somatic hospitals and six psychiatric units (N = 263 [response rate, 52%], 23 care processes) using a Norwegian versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Gittell indicated that team functions are strong when the reported RC scores are ≥4 on a five-point scale, which was found for nine of the 15 teams included in this study [ 10 ]. An earlier study investigating RC in 23 teams from six somatic hospitals and six psychiatric units in Western Norway found that 14 of 23 teams had a RC score below 3.4, which was the lowest score for rehabilitation teams in the present study [ 30 ]. Further, in this previous study, half of the teams showed relationship scores below 3.8, compared with only one rehabilitation team in the present study [ 30 ].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Gittell indicated that team functions are strong when the reported RC scores are ≥4 on a five-point scale, which was found for nine of the 15 teams included in this study [ 10 ]. An earlier study investigating RC in 23 teams from six somatic hospitals and six psychiatric units in Western Norway found that 14 of 23 teams had a RC score below 3.4, which was the lowest score for rehabilitation teams in the present study [ 30 ]. Further, in this previous study, half of the teams showed relationship scores below 3.8, compared with only one rehabilitation team in the present study [ 30 ].…”
Section: Discussionmentioning
confidence: 53%
“…An earlier study investigating RC in 23 teams from six somatic hospitals and six psychiatric units in Western Norway found that 14 of 23 teams had a RC score below 3.4, which was the lowest score for rehabilitation teams in the present study [ 30 ]. Further, in this previous study, half of the teams showed relationship scores below 3.8, compared with only one rehabilitation team in the present study [ 30 ]. The RC scores in this study were also high compared with previous international studies, indicating strong team functions for interprofessional teams in rehabilitation centre in Western Norway [ 8 , 26 , 29 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…RC is a self-reporting validated survey measuring team functions among members of interprofessional teams [20, 41]. The RC survey has recently been translated into Norwegian and validated within teams in specialised health care settings [42]. This study found a satisfactory two-factor solution (Cronbach’s alpha in parentheses); RC communication = four items: frequency, accuracy, timeliness and problem-solving ( α = 0.93), RC relationship = three items: shared knowledge, shared goals, mutual respect) ( α = 0.80) [42, 43].…”
Section: Methodsmentioning
confidence: 99%
“…Responses were reported on a 5-point Likert scale (one = never, two = rarely, three = occasionally, four = often and five = always). RC has been used in various health care settings, such as primary health [44], hospital settings [42, 45] and secondary rehabilitation services [18]. RC subscale scores were obtained for all teams ( N = 15) in all rehabilitation centres by conducting a survey among health care professionals ( N = 124, 52% response rate).…”
Section: Methodsmentioning
confidence: 99%